Image Processing and Communications Challenges 10 10th International Conference, IP&C'2018 Bydgoszcz, Poland, November 2018, Proceedings - Choraś, Michał; Choraś, Ryszard S. (Advances in Intelligent Systems and Computing, 2019)
Presenting a collection of high-quality research papers on image processing and communications, this book not only discusses emerging applications of the currently available solutions, but also outlines potential future techniques and research directions in these areas. Gathering the proceedings of the 10th International Conference on Image Processing and Communications (IP&C 2018), held in Bydgoszcz, Poland in November 2018, it is divided into two parts. Part I focuses on image processing, offering a comprehensive survey of available methods and discussing current trends in computer vision. In turn, Part II presents novel results on networks, communications and a diverse range of applications, including cybersecurity and cloud computing. .